Analyses of fixed effects for genetic evaluation of dairy cattle using test day records in Indonesia - Anang, Asep; Indrijani, Heni; Tasripin, Didin (Indonesian Animal Sciences Society, 2010)
Season, rainfall, day of rain, temperature, humidity, year and farm are fixed effects, which have been reported to influence milk yield. Those factors are often linked together to contribute to the variation of milk production. This research is addressed to study the fixed effect factors, including lactation curve, which should be considered for genetic evaluation of milk yield based on test day records of dairy cattle. The data were taken from four different farms, which were PT. Taurus Dairy Farm, BPPT Cikole, Bandang Dairy Farm, and BBPTU Baturraden. In total of 16806 test day records were evaluated, consisting of 9,302 at first and 7,504 at second lactation, respectively. The results indicated that fixed effects were very specific and the influences had different patterns for each farm. Consequently, in a genetic evaluation, these factors such as lactation, temperature, year, day of rain, and humidity need to be evaluated first.Â Ali-Schaeffer curve represented the most appropriate curve to use in the genetic evaluation of dairy cattle in Indonesia. Key words: Fixed Effects, Milk Production Curve, Test Day, Dairy Cattle